A Plant design for the manufacture of sulfated monoglyceride and diglyceride detergent bars - Aguilar, Ma. Elena; Barot, Ma. Patricia Lourdes R.; Laxamana, Benedicto; Paita, Loudes (College of Engineering, 1982)
Capacity: 14 metric tons detergent/day -- Fixed capital investment: P 44,665,354.34 -- Annual sales at maximum production: P 50,414,400.00 -- Pay-out time: 3.91 years -- Break-even point: 65.057% of maximum production -- Shut-down point: 5.04% maximum production -- Percent return on investment: 15.55%